Historical biogeography of the Gondwanan freshwater genus Boeckella (Crustacea): Timing and modes of speciation in the Southern Hemisphere. Issue 12 (14th September 2021) - Maturana, Claudia S.; Rosenfeld, Sebastián; Biersma, Elisabeth M.; Segovia, Nicolás I.; González‐Wevar, Claudio A.; Díaz, Angie; Naretto, Javier; Duggan, Ian C.; Hogg, Ian D.; Poulin, Elie; Convey, Peter; Jackson, Jennifer A.
Abstract: Aim: We investigated evolutionary relationships and biogeographical patterns within the genus Boeckella to evaluate (1) whether its current widespread distribution in the Southern Hemisphere is due to recent long‐distance dispersal or long‐term diversification; and (2) the age and origin of sub‐Antarctic and Antarctic Boeckella species, with particular focus on the most widely distributed species: Boeckella poppei . Location: South America, sub‐Antarctic islands, maritime Antarctica, continental Antarctica and Australasia. Methods: To reconstruct phylogenetic patterns of Boeckella, we used molecular sequence data collected from 12 regions and applied Bayesian and Maximum Likelihood analyses using multiple loci. We also estimated divergence times and reconstructed ancestral ranges using two different models of species evolution. Results: Phylogenetic analyses and divergence time estimates suggested that Boeckella originated on the Gondwanan supercontinent and initially split into two main clades during the late Cretaceous ( ca . 80 Ma). The first clade diversified in Australasia, and the second clade is currently distributed in South America, various sub‐Antarctic islands and Antarctica. Dispersal from South America to the Kerguelen and Crozet archipelagos occurred during the Eocene/Oligocene ( B . vallentini ) and in the late Pliocene ( B . brevicaudata ), while South Georgia and the maritime Antarctic were likely colonized during the late Pleistocene ( B . poppei ). Main conclusions: Boeckella has a Gondwanan origin, with further diversifications after the physical separation of the continental landmasses. Extant populations of Boeckella from the Scotia Arc islands and Antarctic Peninsula originated from South America during the Pleistocene, suggesting that original Antarctic Gondwanan lineages did not survive repeated glacial cycles during the Quaternary ice ages. A continuous decline in the species accumulation rate is apparent within the genus as the early Eocene, suggesting that Boeckella diversification may have decreased due to progressive cooling throughout the Cenozoic era.